The Performance Of The Initial Public Offerings (IPOs) On Second And Mesdaq Board In Bursa Malaysia - Cheng, Yen Toa (2005)
This study empirically investigates the aftermarket performances of Initial Public Offerings (IPOs) of the Second and MESDAQ Board in Bursa Malaysia over 1993 to 2004. The entire population of 254 IPOs in Second Board and 41 IPOs in MESDAQ Board were studied to test the performance over a period of time.